Serum amino acid concentrations in nine athletes before and after the 1993 Colmar ultra triathlon - Lehmann, M.; Huonker, M.; Dimeo, F.; Heinz, N.; Gastmann, U.; Treis, N.; Steinacker, J. M.; Keul, J.; Kajewski, R.; Haussinger, D. (International Journal of Sports Medicine, 1995)
The amino acid imbalance hypothesis should explain the fatigue originating in the brain during sustained exercise or over-training as a branched-chain (BCAA)/aromatic amino acids (AAA) imbalance with increased brain tryptophan uptake and 5-hydroxytryptamine synthesis. The serum amino acid profile was determined in 9 ultra-triathletes before and after completing the 1993 Colmar ultra-triathlon to additionally analyse the extent of this amino acid imbalance during such an extreme prolonged contest lasting more than 23 hours. The summed serum concentration of 25 amino acids decreased by 18% from 3962 +/- 846 to 3255 +/- 694 umol.l-1 likely reflecting a catabolic state of the organism with a decrease in 18 individual amino acids by 9-56%, an increase in cystine (+38%), methionine (+24%), tyrosine (+10%), phenylalanine (+12%), free tryptophan (+74%), and constant glutamine, leucine and total tryptophan levels. Since plasma volume increased by approximately 7.6% with a 3.3 kg body mass decrease in the athletes during the ultra triathlon, a decrease in intra-cellular water with an extra-cellular fluid increase is hypothesized. This decrease in cellular hydration state is seen as a protein-catabolic signal.